If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -1y = 9 Add '-9' to each side of the equation. 9 + -9 + -1y = 9 + -9 Combine like terms: 9 + -9 = 0 0 + -1y = 9 + -9 -1y = 9 + -9 Combine like terms: 9 + -9 = 0 -1y = 0 Solving -1y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-1'. y = 0 Simplifying y = 0
| 15x-45+3x=18x+18-13 | | x+0.07x=16.05 | | 9x-1=8x+19 | | (9x+2)/5=4 | | (3x^2+2x-9)-(-3x+4)= | | -3-y=9 | | (3y/2a)/(8a^2y5/15y) | | 6x^2+2x-58=0 | | 2.3x-9.34=6.3 | | 4/17(x)=20 | | 3x-14=2x+19 | | -40-3x=14-10x | | 3-2(1/7) | | 8c+c=27 | | -4y-2+3y+4=-5 | | 24w^9x^6y-22x^4y^6= | | 2(1/7) | | 1x-6=3x-4 | | -[4(7)+2]-[3(7)-4]=x | | 4b+29=48 | | -[4(7)+2]-[3(7)-4]=-5 | | 3-21/7 | | y=3x+6graph | | 60=-5x+9 | | -(4y+2)-(-3y-4)=-5 | | 4+4y=8 | | 0=16t^2-30t+13 | | 6x-59=4x-9 | | 1+4y=8 | | 3(x+4x)=30-10x | | -2(10)+4=-8 | | 0=45-5t-5t^2 |